KEAMANAN MARITIM DARI ASPEK REGULASI DAN PENEGAKAN HUKUM (MARITIME SECURITY FROM THE ASPECTS OF REGULATION AND LAW ENFORCEMENT) - Shanti Dwi Kartika (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2014)
Indonesia with the geographical conditions and the potential for natural resources is recognized as an archipelagic state and a maritime country. This also puts Indonesia as the centre of gravity and the global supply chain system. This condition causes the Indonesian suffer threats, harassment, and constraints as a consequence of the condition that has implications for maritime security of the country. This position must be supported with security and defense system strong and changing patterns of national development that is not only oriented dimension of land but also oriented to naval. For it has been established several policies and regulations, but to date these regulations are still sectoral causing disharmony and overlapping rules and authority in maritime security. This also applies to the system of law enforcement and state sovereignty in the sea which are affected by the legislation. On that basis, the regulatory aspects of maritime security and law enforcement needs to be done harmonization of legal systems and legislation, promptly resolve and determine the state borders both on land, sea, and air, and pointed to the Navy’s most responsible for maritime security and serves as a leading sector.ABSTRAKIndonesia dengan kondisi geografis dan potensi sumber daya alamnya diakui sebagai negara kepulauan dan negara maritim. Ini juga menempatkan Indonesia sebagai centre of gravity and the global supply chain system. Kondisi ini menyebabkan Indonesia mengalami ancaman, gangguan, dan kendala yang berimplikasi pada keamanan maritim negara. Kedudukan ini harus didukungdengan sistem pertahanan dan keamanan yang tangguh dan mengubah pola pembangunan nasional yang tidak hanya berorientasi pada matra darat tetapi juga berorientasi pada matra laut. Untuk itu, telah ditetapkan beberapa kebijakan dan regulasi, namun sampai saat ini regulasi tersebut masih bersifat sektoral sehingga timbul disharmoni dan tumpang tindih peraturan dankewenangan dalam keamanan laut. Ini juga berlaku bagi sistem penegakan hukum dan kedaulatan negara di laut yang dipengaruhi oleh peraturan perundang-undangan tersebut. Atas dasar itu, maka keamanan maritim dari aspek regulasi dan penegakan hukum perlu dilakukan harmonisasi sistem hukum dan peraturan perundang-undangan, segera menyelesaikan dan menentukan batas wilayah negara baik di darat, laut, dan udara, serta menunjuk TNI AL yang paling bertanggung jawab terhadap keamanan maritim dan berfungsi sebagai penanggung jawab sektor.